(untitled) (World Bulletin of Management and Law, 2022)
In modern economic conditions, the activity of each enterprise is the subject of attention of a wide range of market participants interested in the results of its functioning. At the same time, the importance of evaluating the effectiveness and financial condition of business entities sharply increases. The owners analyze the financial condition of the enterprise to increase the return on capital, to ensure a stable position. Lenders and investors study financial reports in order to minimize their risks on loans and deposits, suppliers to receive payments in a timely manner, tax inspectorates to fulfill the budget revenue plan